IT Talent Shortage: Strategies to Mitigate a Blackout - Souza, Ana Carolina Moises de; Reinehr, Sheila; Malucelli, Andreia; Conte, Tayana; Marczak, Sabrina; Jaccheri, Letizia; Binder, Fabio; Lauschner, Tanara; Cruzes, Daniela (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3533, 2024)
The global Information Technology (IT) market was valued at approximately $3,110 million in 2022, marking a 7.4% increase over the previous year. Of this total, around 56% pertained to the software and services sector. This growth poses a global challenge for IT organizations due to a significant gap between the increasing demand for IT skills and the availability of qualified professionals. Currently, about 87% of organizations worldwide are experiencing the effects of this skills gap, hindering business operations. Traditional undergraduate computing programs often require more time than the current market demands can afford. To address this issue, universities and companies are developing innovative educational strategies. Our goal is to share the experience of implementing four distinct cases, three in Brazil and one in Norway, so that other universities and companies can adopt similar strategies to alleviate the IT skills shortage. Therefore, this paper presents strategies for the preparation of IT professionals to mitigate the impacts of the IT labor shortage. Each case includes an experience report on the context, structure, benefits, hard and soft skills developed, and lessons learned. Finally, we summarize the contributions of these four cases by reflecting on their differences and similarities, followed by a summary of the strategies that proved effective in collaborating with companies.